Prevalence and risk factors for microalbuminuria in a cross-sectional study of type-2 diabetic patients in Indonesia : a subset of DEMAND study (Medical Journal of Indonesia, 2009)
Aims Microalbuminuria (MA) is a strong predictor of diabetic nephropathy and cardiovascular morbidity and mortality in patients with type-2 DM. The present study aimed to gather information on the prevalence and risk factors for MA in Indonesian patients with type-2 DM.Methods The DEMAND study was an international open cross-sectional 1-day survey on microalbuminuria prevalence and its risk factors in type-2 diabetic patients. This study reports the results of the Indonesian survey which was performed in primary care practice in Indonesia from June to December 2003. Normotensive or hypertensive adult patients of both genders with type-2 DM without known proteinuria and/or kidney disease were recruited into the study. Patients with known pregnancy, having menstruation or acute fever were excluded. A single urinary albumin/creatinine test was carried out in all patients.Results A total of 770 patients were eligible for analysis. Approximately 80% of the patients had micro-/ macroalbuminuria, while renal insufficiency was detected in about 36% of the 433 patients with available data. Target HbA1c (< 7%) was reached by only 40% of the 118 patients who had HbA1c values. Most antidiabetic treatment prescribed was oral (82%), while insulin was used by only 14% of patients. Goal BP (< 130/80 mm Hg) was achieved in only 9% of patients. The frequency of patients receiving antihypertensives was 52%, statins 18%, and aspirin 26%. The most frequently used antihypertensives were RAS blockers (45%), while diuretics were used in 7 % of the patients. The family history of DM was found in 43% of patients, the history of retinopathy in 16%, diabetic foot 9%, and history of smoking in 20% of patients.Conclusion These data reveal that Indonesia has one of the highest frequencies of silent diabetic kidney disease seen in any national group in the global DEMAND Study. Early detection, monitoring of vascular complications, and more aggressive multifactorial treatment aiming at renal and vascular protection are urgently needed for Indonesian patients with type-2 diabetes. (Med J Indones 2009; 18: 124-30)Key words: microalbuminuria, type-2 DM, Indonesia, DEMAND study